The prognostic relevance of full-thickness burns on ABSI - Gorenflo, Johanna; Reichert, B.; Reif, S.; Megas, I. -F.; Billner, M. (Burns, 2024)
Introduction - The Abbreviated Burn Severity Index (ABSI) by Tobiasen, which is commonly used to estimate the mortality risk of severely burned patients, calculates an additional point for the existence of full-thickness (third-degree) burns. [1] However, the score does not consider the extent of the body surface affected by third-degree burns. To understand whether there is a way to improve ABSI prediction power, this study aims to determine the influence of full-thickness burns on survival rates and how it affects the predictive precision of the ABSI. - Material and methods - In this study, the statistical evaluation of 2538 patients collected prospectively in the context of the German Burn Registry was carried out. A linear regression analysis was carried out to show the prognostic relevance of full-thickness burns. Age, sex, total body surface area burned (TBSA), and the presence of inhalation injury were also observed as further influencing factors. - Results - Among the 2538 patients meeting our inclusion criteria, full-thickness burns were found in 1233 patients. In patients with a TBSA below 20 %, the extent of full-thickness burns is not relevant to the prognosis in terms of survival probability (p = 0.124). With more than 20 % TBSA, the extent of third-degree burns is of significant relevance (p = 0.000). In patients without full-thickness burns and calculated ABSI values ≥ 12 the survival rate of 46 % was noticeably better than the predicted survival rate of < 10 % according to the ABSI Score, whereas the predicted survival rate in patients with third-degree burns (< 10 %), closely matched the observed survival rate of 11 %. - Conclusion - For patients with a TBSA < 20 %, the presence of full-thickness burns is not relevant for survival. In contrast to this observation, the percentage of full-thickness burns is of crucial prognostic importance for patients with a TBSA of > 20 %. By adjusting the ABSI and taking into account the exact percentage of third-degree burns, an improvement in the prognostic precision of the score could be achieved.
Online verfügbar: 6. Juli 2024, Artikelversion: 5. Dezember 2024
Gesehen am 14.03.2025